ELISA‐based quantification of neurotrophic growth factors in urine from prostate cancer patients. Issue 11 (17th August 2021) - March, Brayden; Lockhart, Kathleen Rebecca; Faulkner, Sam; Smolny, Markus; Rush, Robert; Hondermarck, Hubert
Abstract: Non‐invasive procedures are needed for prostate cancer management, and urine represents a potential source of new biomarkers with translational value. Recent evidence has shown that the growth of new nerves in the tumor microenvironment is essential to prostate cancer progression. Neurotrophic growth factors are expressed by prostate cancer cells and contribute to prostate tumor innervation, but their presence in urine is unclear. In the present study, we have assayed the concentration of neurotrophic factors in the urine of prostate cancer patients. Urine was collected from a prospective cohort of 45 men with prostate cancer versus 30 men without cancer and enzyme‐linked immunosorbent assay was used to quantify nerve growth factor (NGF) and its precursor proNGF, brain‐derived neurotrophic factor (BDNF) and proBDNF, neurotrophin‐3, neurotrophin‐4/5, and glia‐derived neurotrophic growth factor. The results show that neurotrophic factors are detectable in various concentrations in both cancer and healthy urine, but no significant difference was found. Also, no association was observed between neurotrophic factor concentrations and prostate cancer grade. This study is the first quantification of neurotrophins in urine, and although no significant differences were observed between prostate cancer patients versus those without prostate cancer, or between prostate cancers of various grades, the potential value of neurotrophins for prostate cancer diagnosis and prognosis warrants further investigations in larger patient cohorts.